1978
DOI: 10.1136/hrt.40.5.468
|View full text |Cite
|
Sign up to set email alerts
|

The floppy mitral valve. Study of incidence, pathology, and complications in surgical, necropsy, and forensic material.

Abstract: SUMMARY In the study of 1984 routine hospital necropsies the mitral valve was examined from the left atrium in the intact heart with a pressure head of water in the left ventricle. The valve was graded from grade 0 (normal) to grade 4: grade 1, expansion of a small part of one cusp only; grade 2, over one-third of the posterior cusp or one-half of the anterior cusp expanded, with intact chordae; grade 3, ruptured chordae; grade 4, chordal fusion to ventricular wall. The frequency ofgrade 2 to 4 floppy valves r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
1
2

Year Published

1981
1981
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(92 citation statements)
references
References 58 publications
3
83
1
2
Order By: Relevance
“…33) In another study, the concordance between inadequate production of type III collagen and echocardiographic findings of MVP in patients with type IV Ehler-Danlos syndrome have suggested that this collagen abnormality may be the responsible factor in patients with this syndrome. 34) Abnormalities of collagen have been found in myxomatous or floppy valves of patients with MVP [11][12][13] that coincide with those identified in skin biopsies of patients with hypermobility syndrome 9) leading to the suggestion of a common pathogenetic mechanism of abnormal production or maturation of collagen. 14) Several clinical observations have led to the speculation that primary MVP syndrome represents a generalized disorder of connective tissue.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…33) In another study, the concordance between inadequate production of type III collagen and echocardiographic findings of MVP in patients with type IV Ehler-Danlos syndrome have suggested that this collagen abnormality may be the responsible factor in patients with this syndrome. 34) Abnormalities of collagen have been found in myxomatous or floppy valves of patients with MVP [11][12][13] that coincide with those identified in skin biopsies of patients with hypermobility syndrome 9) leading to the suggestion of a common pathogenetic mechanism of abnormal production or maturation of collagen. 14) Several clinical observations have led to the speculation that primary MVP syndrome represents a generalized disorder of connective tissue.…”
Section: )mentioning
confidence: 99%
“…6) In the following years, a high incidence of MVP has been reported in patients with benign joint hypermobility syndrome (BJHMS), 7,8) which, like MVP, is inherited mainly as a sex-influenced dominant trait. 9,10) Abnormalities of collagen have been found in myxomatous or floppy valves of patients with MVP [11][12][13] that coincide with those identified in skin biopsies of patients with hypermobility syndrome 9) leading to the suggestion of a common pathogenetic mechanism of abnormal production or maturation of collagen. 14) However, there have been a few studies on the relation between the echocardiographic features of mitral valves [anterior mitral leaflet thickness (AMLT), 15) maximal leaflet displacement (MLD), 7) degree of mitral regurgitation (DMR)], elastic properties of the aortic wall [index of aortic systolic (AOSDI) and diastolic diameters (AODDI), index of aortic stiffness (IAOS) and aortic distensibility (AOD)], and Beighton hypermobility score (BHS) in MVP patients with BJHMS.…”
mentioning
confidence: 99%
“…The grade of these changes is in part genetically determined and in part age related. 12 16 Therefore, multivalvular regurgitation of little or no clinical significance can be expected to occur in older subjects. The purpose of this study was to investigate the prevalence of valvular regurgitation in the aged by pulsed Doppler echocardiography.…”
mentioning
confidence: 99%
“…Klinik çalışmalarda mitral kapak prolapsusunun prevalansı %2,4 olarak bildirilirken (2) otopsi serilerinde insindansı %18'e kadar çıkmaktadır (3 Nishimura ve ark. (6) 237 hastalık uzun dönem (ortalama 6,2 yıl) bir takip çalışmasında, redundan mitral kapakların ani ölüm, infektif endokardit, serebral emboli gibi ölümcül komplikasyonlar için muhtemel bir risk oluşturduğunu tanımlamışlardır.…”
Section: Discussionunclassified